Clinical, mechanical and biochemical observations on wound healing in bovine : An experimental study on biological dressings - LINGARAJ, H D; MOGHA, I V; RAO, V K (The Indian Journal of Animal Sciences, 2013)
Fresh porcine skin, fresh anmion and amnion preserved in silver nitrate (0.5%) were evaluated as biological dressing material in bovine experimental wounds. Clinically treated wounds performed better than control. Granulation tissue appearance, contraction and epithelialization was relatively slow in wounds dressed with porcine skin than in amnion treated wounds. The rate of wound contraction increased significantly from day 3 onwards in all the wounds. Breaking strength, tensile strength, extensibility. energy absorption and collagen, hydroxyproline and elastin Contents steadily increased up to day 28. Higher increase was recorded in preserved amnion-dressed wounds, followed by fresh amnion, porcine-skin-treated wounds and control wounds. The amount of hexosamine decreased from day 3 to dny 28 in all the wounds and the rate of decrease was faster in the wounds treated with preserved amnion.